Combined effect of curing temperature, curing period and alkaline concentration on the mechanical properties of fly ash-based geopolymer - Pudasaini Sajan (Elsevier, 2021)
This paper presents a comprehensive study of the impacts of three governing factors: Alkaline concentration, curing temperature and curing period on the mechanical properties of a geopolymer that include the uniaxial compressive strength, Poisson’s ratio, and Young’s modulus of elasticity. As literature review indicates, most of the previous research studies were focused on the effect of single factor, while there is a lack of comprehensive studies to simultaneously investigate the combined effects of all these factors, especially in a systematic experimental setup. Acknowledging this rarely exploited area of geopolymer research, this work developed a sequential experimental setup to perform a detailed study to understand the mechanical behaviors of the geopolymer as a function of alkaline concentration, curing temperature and curing period. The test results show that the compressive strength of geopolymer is mostly governed by the curing temperature as compared to alkaline concentration and curing period. Geopolymer samples cured at 60 °C and 80 °C give a competitive compressive strength of about 30 MPa even when prepared with less alkaline activator and cured for a shorter period. This observation is justified by the microscopic analysis of samples at each curing temperature that explains the formation of microcracks, amount of unreacted fly ash, sodium-aluminosilicate hydrate crystals (NASH), calcium-silicate hydrate (CSH) crystals and efflorescence.